Application of DSM in process management of a PE commercial real estate development project. Issue 1 (19th February 2018) - Ma, Guofeng; Zhu, Tiancheng
Abstract : Purpose: After the drawbacks in the process management of China PE commercial real estate development project are analyzed, it is necessary to introduce a more integrated and advanced tool to solve them. The paper aims to discuss this issue. Design/methodology/approach: A standard process model was proposed first. Based on the model, a coupled activity dependency model was also built by structural tool design structure matrix (DSM), the detailed matrix involving 119 activities and 322 information dependencies. Next, two large processes coupled blocks were generated by the sequencing algorithm and tearing algorithm. Then, the general simulation framework with rework probability and rework effect was introduced to do empirical research for one of the activities blocks due to the merit of solving rework of DSM. Findings: These results showed that key activities were rearranged, that information interactive scope for them was optimized and that collaborative organization interface was built. And the expected duration after simulation was 131 days at 90 percent percentile, providing the objective basis of process arrangement to some extent and decreasing the risk of prospective yields during fund period. Originality/value: This paper is a qualitative and quantitative practical research for the process management of PE commercial real estate development projects in China based on a real project which has begun construction in 2014.